2017
DOI: 10.1016/j.redox.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Exercise redox biochemistry: Conceptual, methodological and technical recommendations

Abstract: Exercise redox biochemistry is of considerable interest owing to its translational value in health and disease. However, unaddressed conceptual, methodological and technical issues complicate attempts to unravel how exercise alters redox homeostasis in health and disease. Conceptual issues relate to misunderstandings that arise when the chemical heterogeneity of redox biology is disregarded: which often complicates attempts to use redox-active compounds and assess redox signalling. Further, that oxidised macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 144 publications
(181 reference statements)
2
61
0
1
Order By: Relevance
“…Applying how mitochondria produce O 2 .− /H 2 O 2 to an active and inactive synapse reveals an activity dependent dichotomy: neuronal activity decreases whereas inactivity increases mitochondrial O 2 .− /H 2 O 2 production. Consistent with experimental data in skeletal muscle wherein contractile activity (i.e., exercise) decreases whereas inactivity increases mitochondrial O 2 .− /H 2 O 2 production . In addition, silencing NMJ activity with neurotoxins or endogenous synapse pruning cues increases mitochondrial (O 2 .− /H 2 O 2 ) in vivo .…”
Section: Mitochondrial Ros Are Endogenous Synaptic Activity Sentinelssupporting
confidence: 87%
See 1 more Smart Citation
“…Applying how mitochondria produce O 2 .− /H 2 O 2 to an active and inactive synapse reveals an activity dependent dichotomy: neuronal activity decreases whereas inactivity increases mitochondrial O 2 .− /H 2 O 2 production. Consistent with experimental data in skeletal muscle wherein contractile activity (i.e., exercise) decreases whereas inactivity increases mitochondrial O 2 .− /H 2 O 2 production . In addition, silencing NMJ activity with neurotoxins or endogenous synapse pruning cues increases mitochondrial (O 2 .− /H 2 O 2 ) in vivo .…”
Section: Mitochondrial Ros Are Endogenous Synaptic Activity Sentinelssupporting
confidence: 87%
“…Consistent with experimental data in skeletal muscle wherein contractile activity (i.e., exercise) decreases whereas inactivity increases mitochondrial O 2 .À /H 2 O 2 production. [30,31] In addition, silencing NMJ activity with neurotoxins or endogenous synapse pruning cues increases mitochondrial (O 2 .À /H 2 O 2 ) in vivo. [32] The above-mentioned theoretical and experimental evidence strongly suggests that: .À /H 2 O 2 are energetically efficient synaptic activity sentinels because their production has no ATP cost [21] and reports, in part, on the rate of mitochondrial ATP synthesis.…”
Section: Applying How Mitochondria Produce Omentioning
confidence: 99%
“…Oxidative stress (OS) can be defined as a state of cellular imbalance between the production and the physiological capacity to neutralize reactive species [1]. Current understanding of this phenomenon includes the potential damage that this imbalance may inflict to macromolecules, such as lipids, proteins, and deoxyribonucleic acid (DNA) [2]. Also, decreased control of mitochondrial respiration and decreased integrity of the sarcoplasmic reticulum are known to be OS related [3].…”
Section: Introductionmentioning
confidence: 99%
“…12,17 Stone et al 13 were the first to assess the muscle damage response to 90 min soccer-simulation protocol (SSP) played on AT and NG and reported that blood creatine kinase (CK) concentration was similar for both surfaces immediately and up to 48 hours post-test. Since CK is just one indicator of muscle damage and two or more biomarkers are recommended to accurately infer muscle damage, 18 further studies using multiple biomarkers (e.g., CK and lactate dehydrogenase (LDH)) 19,20 are required to robustly address the influence of surface-type on muscle damage responses following physical exercise. Moreover, the effect of playing surface on biomarkers of immune response [e.g., neutrophils (NEU), monocytes (MON), and lymphocytes (LYM)], 21,22 inflammation [e.g., C-reactive protein (CRP)], 23,24 metabolism (e.g., Lac and glucose (GLC)), 25 and perceptual responses during exercise has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%